Disfuncionalidad familiar y salud emocional en los estudiantes de la Unidad Educativa Nicolás Infante Diaz - Vasquez Arevalo, Zandra Dayanna (2019)
Family dysfunctionality is a common problem in society and unfortunately has become a daily family that is formed by conflict, misconduct, screaming, insults and often assaults by members who belong to the home, leading to parents and children to accommodate themselves to such actions and not to be cautious about what may affect the healthy part of the person both physically and psycho-emotionally. The objective of this research is to analyze the incidence of family dysfunction in emotional health in the students of the Nicolás Infante Díaz Educational Unit. In order to carry out this project, we worked with 100 students, 100 parents of families and 20 teachers. A questionnaire of eight questions about family dysfunction and emotional health was applied to the aforementioned sample, so their support was requested and they responded with all the sincerity to carry out this problem that exists in the Educational Unit. In order to establish results for further analysis and interpretation. These results gave a guide in the elaboration of the proposal of application of the present investigative project, having as proposal to apply awareness workshops of the family dysfunctionality to improve the emotional health of the students.